Comparison of Resting Energy Expenditure Assessment in Pediatric Oncology Patients. (2nd February 2018) - Ringwald‐Smith, Karen; Hobar, Ashley; Flowers, Casey; Badgett, Katie; Williams‐Hooker, Ruth; Roach, Robin R.; Sykes, April; Lu, Zhaohua; Mackert, Paul; Mandrell, Belinda N.
Abstract: Background : Evaluation of energy requirements is an important part of the nutrition assessment of pediatric oncology patients. Adequate provision of energy in this population is of extreme importance because of the prevalence of malnutrition and its effect on growth, development, quality of life, morbidity, and mortality. Numerous methods are used in clinical practice for estimating the resting energy expenditures (REE), specifically indirect calorimetry and predictive equations. A relatively new instrument used to assess REE is the hand‐held indirect calorimeter. The purpose of this quality improvement project was to compare the accuracy of REE measurements taken by a hand‐held indirect calorimeter and predictive equations to that of a standard indirect calorimeter metabolic cart. Methods : Patients receiving therapy for pediatric cancer, aged 7–18 years, and having a weight ≥15 kg and scheduled for a REE nutrition assessment were eligible. Sequentially, the patient's REE was assessed with the cart and the hand‐held indirect calorimeter along with the predictive equation calculation. Results : Post hoc pairwise comparisons revealed that all 3 methods were significantly different from one another ( P < .0001). When compared with the cart, the portable hand‐held calorimeter was found to underestimate REE by 11.9%, whereas predictive equations overestimated REE by 12.4%. Conclusion : Our quality improvement project suggests that the hand‐held indirect calorimeter underestimated REE, and predictive equations overestimated REE in pediatric oncology nutrition assessment. Therefore, we recommend that these limitations in assessment be considered when assessing REE using a hand‐held indirect calorimeter or predictive equations.